2017
DOI: 10.1038/bjc.2017.32
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of polypyrimidine tract-binding protein 3 induces apoptosis and cell cycle arrest, and enhances the cytotoxicity of 5- fluorouracil in gastric cancer cells

Abstract: Background:Human polypyrimidine tract binding protein 3 (PTBP3) was first discovered in 1999 and has been well characterised as a differentiation regulator. However, its role in human cancer has rarely been reported. Our previous study revealed increased PTBP3 protein level in gastric cancer tissues. Downregulation of PTBP3 suppressed the proliferation and differentiation of gastric cancer cells in vivo.Methods:PTBP3 mRNA levels in human gastric cancer and adjuvant non-tumour tissues were detected. Apoptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
8
18
0
Order By: Relevance
“…In gastric cancer, PTBP3 contributes to the cancer metastasis by mediating CAV1 alternative splicing (Liang et al, 2018). Inhibition of PTBP3 induces apoptosis and cell cycle arrest, and enhances the cytotoxicity of 5-fluorouracil in gastric cancer cells (Liang et al, 2017). The present study demonstrated, for the first time, that miR-29a/PTBP3 is regulated by ILF3-AS1 in GC.…”
Section: Discussionsupporting
confidence: 57%
“…In gastric cancer, PTBP3 contributes to the cancer metastasis by mediating CAV1 alternative splicing (Liang et al, 2018). Inhibition of PTBP3 induces apoptosis and cell cycle arrest, and enhances the cytotoxicity of 5-fluorouracil in gastric cancer cells (Liang et al, 2017). The present study demonstrated, for the first time, that miR-29a/PTBP3 is regulated by ILF3-AS1 in GC.…”
Section: Discussionsupporting
confidence: 57%
“…1b ). These results were consistent with our previous study 31 . Our previous study also found that PTBP3 expression is associated with lymph node metastasis.…”
Section: Resultssupporting
confidence: 94%
“…Both cell death and cellular senescence are important responses to stress-associated stimuli. It was demonstrated that 5-FU exerts anticancer effects mainly by inhibiting tumor cell proliferation, activating Bax and P53, and/or caspase-dependent mechanism [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Annexin V/Propidium iodide (PI) staining assay is commonly applied to discern necrotic cells and apoptotic cells, further to quantify apoptosis.…”
Section: Resultsmentioning
confidence: 99%